Crystal structure of a tankyrase 1–telomere repeat factor 1 complex. Issue 4 (1st April 2016) - Li, Bo; Qiao, Ruihong; Wang, Zhizhi; Zhou, Weihong; Li, Xin; Xu, Wenqing; Rao, Zihe
Abstract : Tankyrase 1 (TNKS1) regulates the activity of telomere repeat factor 1 (TRF1) through PARylation. Here, the crystal structure of a complex between TRF1 (residues 1–55) and the second and third ankyrin‐repeat clusters of TNKS1 is presented. Abstract : Telomere repeat factor 1 (TRF1) is a subunit of shelterin (also known as the telosome) and plays a critical role in inhibiting telomere elongation by telomerase. Tankyrase 1 (TNKS1) is a poly(ADP‐ribose) polymerase that regulates the activity of TRF1 through poly(ADP‐ribosyl)ation (PARylation). PARylation of TRF1 by TNKS1 leads to the release of TRF1 from telomeres and allows telomerase to access telomeres. The interaction between TRF1 and TNKS1 is thus important for telomere stability and the mitotic cell cycle. Here, the crystal structure of a complex between the N‐terminal acidic domain of TRF1 (residues 1–55) and a fragment of TNKS1 covering the second and third ankyrin‐repeat clusters (ARC2‐3) is presented at 2.2 Å resolution. The TNKS1–TRF1 complex crystals were optimized using an `oriented rescreening' strategy, in which the initial crystallization condition was used as a guide for a second round of large‐scale sparse‐matrix screening. This crystallographic and biochemical analysis provides a better understanding of the TRF1–TNKS1 interaction and the three‐dimensional structure of the ankyrin‐repeat domain of TNKS.